Dreams and lives in Ottoman Istanbul - Niyazioğlu, Aslı.
1 online resource
Keywords: Dreams and Lives in Ottoman Istanbul explores biography writing and dream narratives in seventeenth-century Istanbul. It focuses on the prominent biographer 'Ata'i (d. 1637) and with his help shows how learned circles narrated dreams to assess their position in the Ottoman enterprise. This book demonstrates that dreams provided biographers not only with a means to form learned communities in a politically fragile landscape but also with a medium to debate the correct career paths and social networks in late sixteenth and early seventeenth-century Istanbul.